KEEFEKTIFAN MEDIA LAPTOP SI UNYIL DALAM PEMBELAJARAN TEKS PROSEDUR KOMPLEKS - Sulistiyono, Roni (Universitas Ahmad Dahlan, 2017)
Creative educators are educators who are able to utilize the media around as a means of learning. One of the television shows that can be utilized as a complex text learning media is a show of Laptop Si Unyil. The impression is about the process of making something or the use of the tool described in a coherent manner. Based on the results of experiments on students PBSI, FKIP, UAD, this show is able to provide better learning outcomes to the group taught by using media Si Unyil Laptop. It can be proved by t-test among groups. Based on posttest data of experimental group and control group obtained t count equal to -2,575 with indigo df equal to 43 and value p = 0,012 at significance level 0,05 (5%). The p value <from the significance level is 0.05 (0.012 <0.05). Impressions Siy Unyil laptop is able to provide effectiveness in learning the text of complex procedures on students PBSI, FKIP, UAD who are following the lecture of Indonesian Language. This is evidenced from the calculation of t-test data pretest and posttest in the experimental group obtained the result that the value of t arithmetic -3.924 denagan value df 42 and significance 0.000. Result of t-test of pretest and posttest data in experiment group obtained p value smaller than significance level 0,05 (0,000 <0,05).